Pengaruh Budget Participation, Asimetri Informasi Dan Budget Emphasis Terhadap Budget Slack Pada PT Wijaya Karya (Persero) Tbk - Alifah, Andi Audy Noor; Sadikin, Dikdik Saleh; Budhijana, R. Bambang (Jurnal Keuangan dan Perbankan, 2024)
This research aims to determine the influence of Budget Participation, Information Asymmetry and budget emphasis on budget slack at PT. Wijaya Karya (Persero) Tbk. The independent variables in this research are Budget Participation, Information Asymmetry and budget emphasis. Meanwhile, the dependent variable is budget slack. The analysis technique for this research uses the PLS or Partial Least Square SmartPLS 4 method. The data collection technique uses a Google Form questionnaire to collect the required information. The results of the number of respondents were 73 employees of PT. Wijaya Karya (Persero) Tbk. The results of the analysis show that Budget Participation has a positive effect on budget slack, information asymmetry has no effect on budget slack, Budget emphasis has no effect on budget slack..